Abnormal Sleep Duration as Predictor for Cardiovascular Diseases: A Systematic Review of Prospective Studies. (7th February 2022) - Laksono, Sidhi; Yanni, Mefri; Iqbal, Mohammad; Prawara, Ananta Siddhi
Abstract : Study Objective . This study is aimed at figuring out the role of abnormal sleep duration in predicting cardiovascular diseases. Methods . We searched the online database PubMed on 30 August 2020 for our data collection. We used the following keywords: sleep duration AND (cardiovascular disease OR cardiovascular event) AND (cohort OR prospective OR retrospective). We identified 653 studies, and after excluding studies that were published before 2015, we obtained 306 studies. After filtering the 306 studies through title and abstract screening and applying the inclusion and exclusion criteria, we further reviewed fourteen studies with full-text reading. We excluded three studies because of insufficient data required and included eleven studies in this systematic review. Results . A total of 361, 041 participants from ten studies were included in this systematic review. The incidence of hypertension, myocardial infarction, coronary artery disease, heart failure, cardiovascular events, and cardiovascular diseases in the short sleep duration group is 46.12%, 0.59%, 5.43%, 0.09%, 7.18%, 1.48%, and 6.8%, consecutively, while the incidence of hypertension, myocardial infarction, coronary artery disease, and heart failure in the long sleep duration group is 30.71%, 0.61%, 6.55%, 1.11%, and 6.04%, consecutively. Nine studies reported an association between sleep duration and cardiovascular diseases while one study reported no association. Seven studies reported that short sleep duration was significantly associated with CVD. Short sleep duration in this study was associated with hypertension and heart failure. Atrial fibrillation and coronary artery disease were associated with both short and long sleep duration. Conclusion . Abnormal sleep duration (short and long sleep duration) may act as the predictor of cardiovascular diseases. The importance of having normal sleep duration should be stressed with other lifestyle modification to avoid the risk of getting cardiovascular diseases. However, further studies are needed to overcome the limitation of this systematic review.